ANALISIS KESANTUNAN BERBAHASA DALAM UNIT KEGIATAN MAHASISWA PERSAUDARAAN SETIA HATI TERATE DI UNIVERSITAS ISLAM NEGERI FATMAWATI SUKARNO BENGKULU: KAJIAN PRAGMATIK - Nurul A'la; Fera Zasrianita; WennyAulia Sari (ISLAMIKA, 2025)
This study, entitled "Analysis of Linguistic Politeness in the Persaudaraan Setia Hati Terate Student Activity Unit at UIN Fatmawati Sukarno Bengkulu: A Pragmatic Study," sought to explore and describe the various manifestations of linguistic politeness within the training processes of the Persaudaraan Setia Hati Terate (PSHT) Student Activity Unit (UKM) at UIN Fatmawati Sukarno Bengkulu. Adopting a qualitative research approach, data were meticulously collected through a combination of observation, audio/video recording, in-depth interviews, and documentation. The primary data source comprised verbal utterances gathered throughout the research period, which were subsequently analyzed using Leech's comprehensive theory of Linguistic Politeness Maxims. The research concludes that the verbal interactions within the PSHT Student Activity Unit at UIN Fatmawati Sukarno Bengkulu are predominantly polite, as demonstrated by consistent adherence to and application of these politeness maxims. The analysis specifically identified patterns of usage: The Tact Maxim was used in five conversations, the Generosity Maxim in four conversations, the Approval Maxim in six conversations, the Modesty Maxim in two conversations, the Agreement Maxim in five conversations, and the Sympathy Maxim in one conversation.